2011
DOI: 10.1007/s11661-011-0673-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Re and Ru on the Solidification Characteristics of Nickel-Base Single-Crystal Superalloys

Abstract: The solidification characteristics, such as the phase transformation temperature and partition coefficient, were investigated in four Ni-base single-crystal superalloys with varied contents of Re and Ru. Differential scanning calorimetry (DSC) analysis reveals that the liquidus and solidus temperatures decrease with increasing levels of Re additions. However, the Ru only has negligible influences on the liquidus and solidus temperatures. The partition coefficient of constituent elements is investigated by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…To assess the solidification distribution coefficients of the individual elements, the point‐matrix scanning technique with the energy‐dispersive spectroscopy (EDS) analysis was used, which was reported in previous studies . The dendritic structure perpendicular to the growth direction was obtained by cutting the cross section from the bars.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the solidification distribution coefficients of the individual elements, the point‐matrix scanning technique with the energy‐dispersive spectroscopy (EDS) analysis was used, which was reported in previous studies . The dendritic structure perpendicular to the growth direction was obtained by cutting the cross section from the bars.…”
Section: Methodsmentioning
confidence: 99%
“…2 shows the DSC curves and solidification characteristic temperatures of experimental alloys. Two obvious exothermic peaks coexisted in the DSC cooling curves of Alloy 1, Alloy 3 and Alloy 4, where the peak at higher temperature represented the solidification of primary phase, and the peak at lower temperature implied the interdendritic region (formed just after the solidification of primary phase) and/or interdendritic precipitation (formed at the last stage of solidification) [31,32]. It is worth noting that in Alloy 3, the heat release of the exothermic peak at lower temperature was significantly higher than those in other alloys, which might indicate that the volume fraction of interdendritic region and/or interdendritic precipitation in Alloy 3 was significantly higher than those of other alloys.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the previous studies indicated undercooling as significantly decreased solidification characteristic temperatures in the DSC cooling curve [31,32]. Herein, only DSC heating curves were used to determine solidification characteristic temperature in this study.…”
Section: Effect Of Al Content On Solidification Characteristic Tempermentioning
confidence: 99%
“…The composition of Pb 39 Bi 25 Sn 36 (wt.%) is indicated on the liquid projection of Pb-Bi-Sn ternary alloy [8][9] (Fig. 1).…”
Section: Solidification Sequence Analyzed By Ternary Phase Diagram Anmentioning
confidence: 99%